Topology optimization of reinforced concrete structures considering control of shrinkage and strength failure. (September 2015) - Luo, Yangjun; Wang, Michael Yu; Zhou, Mingdong; Deng, Zichen
Highlights: Topology optimization for RC structures considering shrinkage effect is presented. Shrinkage of concrete is simulated by introducing a design-dependent force. Concrete failure surface is well fitted by two Drucker–Prager yield functions. The enhanced aggregation method is utilized to reduce the computational effort. Abstract: To take into account the shrinkage effect in the early stage of Reinforced Concrete (RC) design, an effective continuum topology optimization method is presented in this paper. Based on the power-law interpolation, shrinkage of concrete is numerically simulated by introducing an additional design-dependent force. Under multi-axial stress conditions, the concrete failure surface is well fitted by two Drucker–Prager yield functions. The optimization problem aims at minimizing the cost function under yield strength constraints on concrete elements and a structural shrinkage volume constraint. In conjunction with the adjoint-variable sensitivity information, the enhanced aggregation method is utilized to efficiently reduce the computational effort arisen from large-scale strength constraints. Numerical results reveal that the proposed approach can produce a reasonable solution with the least steel reinforcements to ensure the structural safety under the combined action of external loads and shrinkage.